THE INFLUENCE OF PHARMACEUTICAL CARE SERVICES MODEL IN PRESCRIPTION DRUGS ON PHARMACIST’S BEHAVIOR IN PHARMACEUTICAL CARE - Umi Athiyah (UNEJ e-Proceeding)
Pharmaceutical care is an important element inproviding health services that must be integratedwith other elements where pharmacist hasresponsibility in the quality of such cares (Gennaro,2000). Pharmaceutical care is generally based onpharmacist’s responsibilities to guaranteeconformity, effectiveness, and safety of drug therapyby identifying, preventing, as well as solvingproblems of drug therapy received by patient.Pharmaceutical care as a practical guidance isdescribed into three activities: 1) assessing patient’sneeds regarding drug therapy, 2) making care plans,3) following up care plans and evaluating. Anapproach is needed to assess patient’s needsregarding the used drugs which can cover precisionof indication, capable to achieve therapy effects,security and conformity of drug usage.Therapeutic communication between pharmacistand patient becomes the absolute requirement inperforming pharmaceutical care. The finding ofresearch conducted by Research Center of Ministryof Health that was taken in five provinces inIndonesia stated that pharmacist as the person incharge in the lack of communication happened inthe drugstore between pharmacist and consumers inparticular and society in general (Zalbawi, 1991).In the research conducted by Indri MulyaniBunyamin (2005), it was found that 69.9%pharmacists works in the drugstores around DKIJakarta have high quality practices particularly in thepractical management and accountability, but stillhave low pharmaceutical care.The finding of the research on the implementationof pharmaceutical care in prescribed drug servicefound that pharmacists’ activity in assessingprescription completeness, 3.8% bad of doctors’prescription, dentists’ prescription, and veterinaries’prescription; 2.9% bad of drug preparation anddispensing; 21.5% bad of assessment of patient’sdrug therapy; 33.3% bad of making plans forpatient’s drug therapy; 41.9% bad of evaluation andfollowing up patient’s drug therapy (Athiyah, 2005).The finding indicates that pharmacists are stilloriented on drug supply as product, while patient’s needs-oriented which is usually described as theeffort to improve life quality is still ignored.Based on the description and the fact above, thereare lot of issues that must be explored further abouthow pharmaceutical care as a philosophy isimplemented in the form of pharmacists’ taskbehavior in drugstore. Thus, this study examinedpharmacists’ behavior in pharmaceutical care. Thegeneral objective of this study is to createpharmaceutical care model of prescribed drugservice and its influences on the pharmacists’behavior in pharmaceutical care.